Transition of recently retired military generals from military to civilian life - Gatchalian, Jose Francisco H.; Ordojo, Jeffrey E.; Reyes, Clarissa F. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
This was a qualitative study that focused on the transition of recently retired military generals from military to civilian life. The retirees are faced with different challenges after retirement particularly in their transition from military to civilian life. Twenty recently retired military generals from the Armed Forces of the Philippines were each interviewed one on one and a descriptive approach was used to organize the data from their responses. The results showed that the retirees engaged in various activities after military retirement. These activities highlighted the retirees balanced life, sense of leadership, commitment to service, commitment to their faith, and importance of family in their life. In terms of career opportunities after military retirement, the retirees were offered high ranking work opportunities with leadership positions from the civil sector. The retirees emphasized that their military background greatly benefited them in getting these career opportunities. Lastly, data showed that the retirees generally transitioned well into civilian life and did not express much difficulty throughout this transition, as they shared mostly positive experiences and changes from military to civilian life. The study concluded that in order for retirees to transition smoothly into civilian life they must undergo a step by step process which involves finding new activities, setting up expectations, knowing their priorities, choosing between a second career and full time retirement, and assessing their work opportunities. Even as they experienced minor challenges throughout their transition, the retirees overcame them by planning ahead, being proactive, and maintaining discipline in every aspect of their life.
submitted June 2017
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Retired military personnel -- Philippines; Retired military personnel -- Employment .; Retired military personnel -- Life skills guide